The contractiongram: A method for the visualization of uterine contraction evolution using the electrohysterogram. (May 2021) - Batista, Arnaldo G.; Cebola, Ricardo; Esgalhado, Filipa; Russo, Sara; dos Reis, Catarina R. Palma; Serrano, Fátima; Vassilenko, Valentina; Ortigueira, Manuel
Highlights: Uterine Electromyography (Electrohysterography) database representation method. Uterine contractions multichannel temporal representation for single or multiple subjects along the gestational age. Uterine contractions' sequencing in the time and space domains. Sequencing operation includes contraction type such as Alvarez and Braxton-Hicks waveforms. Abstract: Uterine contractions' monitoring has been pointed out as an important tool that may be useful in the preterm risk assessment, term birth estimation and uterine physiology investigation. The multichannel EHG provides a mapping of the myometrium electrical activity projection on the selected channels, providing a wealth of information, including pacemaker regions, signal propagation and contraction amplitude and spectral characteristics. The EHG multichannel data representation, regarding contractile activity, presents an interpretation challenge, given the presence of the multiple contractions of, possibly, different types, in the respective acquisition channels, for different recording sessions and gestational ages of one or multiple pregnant subjects. Typically, an EHG dataset contains data from various subjects, for which multiple recording sessions could be performed, possibly leading to hundreds of recordings. The post-processing step of this data for contraction retrieval may result in multidimensional datasets, requiring interpretation in multiple research scenarios. In this work, a novel representation method is introduced, the Contractiongram, an intuitive graphical tool to facilitate the interpretation of the EHG contractile data for a subject or a whole dataset, throughout the pregnancy, including multisession acquisition scenarios. An application example is presented for a widely used open access EHG database. A contraction detection and classification were a result of a previous research work and used as a data pool for this study. The graphical representation obtained in the current study is a suitable tool for the identification of uterine contraction patterns in selected channels corresponding to different myometrial regions, in designated gestational ages.